INDOOR AIR QUALITY AND HEALTH IN NEWLY CONSTRUCTED APARTMENTS OF INDONESIA: CASE STUDY ON THE EFFECT OF MODIFICATION - Hanief Ariefman Sani; Tetsu Kubota; Usep Surahman; Collinthia Erwindi (Department of Architecture, Institut Teknologi Sepuluh Nopember (ITS), 2021)
In Indonesia, sick building syndrome (SBS) and related health problems are suspected among the residents in emerging new urban houses constructed of modern building materials without sufficient material standards or minimum ventilation rates. First, this study investigates the current conditions of indoor air quality (IAQ) and health in newly constructed high-rise apartments in major cities of Indonesia, in contrast with traditional landed houses, the so-called Kampongs. Concentrations of formaldehyde and TVOC were measured, whereas a face-to-face interview was conducted. A total of 896 respondents were interviewed, and 207 rooms were measured during 2017-2019. The results showed that overall, the newly constructed apartments recorded higher formaldehyde levels compared to Kampongs. The status of the self-reported multiple chemical sensitivity (MCS) among occupants was significantly different between the two building types. Furthermore, the occupants with higher levels of TVOC, in particular, were associated with the higher MCS risks, especially in the apartments. Second, we conducted a modification project in several apartment units of Surabaya to examine the effects of exhaust fans on IAQ. In most units, the concentrations of both formaldehyde and TVOC were reduced after the modification. Further, a follow-up measurement was conducted in the same units for about a month.